Estimation of peak vertical velocity and relative load changes by subjective measures in weightlifting movements - Chapman, Mark; Damian Tomkins, Sam; N Triplett, Travis; Larumbe-Zabala, Eneko; Naclerio, Fernando (Biology of Sport, 2022)
To investigate the ability of the OMNI-RES (0–10) scale to estimate velocity and loading changes during sets to failure in the hang power clean (HPC) exercise. Eleven recreationally resistance-trained males (28.5 ± 3.5 years) with an average one-repetition maximum (1RM) value of 1.1 ± 0.07 kg body mass-1 in HPC, were assessed on five separate days with 48 hours of rest between sessions. After determining the 1RM value, participants performed four sets to self-determined failure with the following relative loading ranges: 60% < 70%, 70 < 80%, 80   90%. The peak vertical velocity (PVV), and Rating of Perceived Exertion (RPE) were measured for every repetition of each set. The RPE expressed after the first repetition (RPE-1) and when the highest value of PVV was achieved during the set (RPE-max) were similar and significantly lower than the RPE associated with a 5% (RPE-5%) and 10% (RPE-10%) drop in PVV. In addition, the RPE produced at failure was similar to RPE-5% only for the heaviest range (≥ 90%). Furthermore, RPE-1 was useful to distinguish loading zones between the four assessed ranges (60 < 70%, vs. 70 < 80%, vs. 80 < 90%, vs. ≥ 90%). The RPE seems to be useful to identify PVV changes (maximal, 5% and 10% drop) during continuous sets to self-determined failure and to distinguish 10% loading zone increments, from 60 to 100% of 1RM in the HPC exercise.